From boredom to excitement: unleashing motivation with Kahoot in English language learning - Abdullah Noori; Asadullah Azimi (Erudita: Journal of English Language Teaching, 2023)
The advent of digital games in language classrooms has ushered in a new era of interactive and dynamic learning experiences. Among these platforms, Kahoot stands out as an engaging and entertaining gaming platform, capturing the attention of both instructors and students. Despite the previous studies on the impact of Kahoot on language learning motivation, they have predominantly focused on assessing the effects of Kahoot before and after instruction overlooking direct comparisons with traditional instructional methods. Consequently, the present study utilized a quasi-experimental research design, and participants were divided into two groups: an experimental group that received instruction using Kahoot, and a control group that followed traditional instructional methods. This research design allowed for a direct comparison of the impact of Kahoot on students’ motivation to learn the language. The results revealed a significant positive impact of Kahoot on students’ motivation to learn English. The students perceived Kahoot as engaging and enjoyable, resulting in heightened enthusiasm and interest in language learning. These findings highlight the transformative potential of Kahoot as a catalyst for enhancing language learning motivation. Integrating Kahoot and other innovative online platforms into EFL instruction can create dynamic, interactive learning environments that foster student engagement and motivation.